Prospects for information and communications technology-enabled services in Kenya: The case of the mobile money transfer industry - Dianah Ngui Muchai; Peter Kiko Kimuyu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The mobile money transfer industry has been the most successful information and communications technology-enabled service in Kenya, having recorded an exponential growth relative to its neighbours within the East Africa region. This could be attributed to Kenya's status as a leading commercial and logistics hub in the region, coupled with the competitive strengths of smaller regional peers such as Rwanda, providing a unique opportunity to expand the industry's services and maximize the economies of scale required for its success and expansion. This can be achieved if Kenya identifies its market niche, generates investment prospects, and addresses the accompanying risks.
Keywords: C19; E42; L86; L88; N27; O55; 330; information and communications-technology-enabled services; prospects; mobile money; Kenya